Stability assessment of Maligcong rice terraces: Linking soil properties and geometry to factor of safety - Rhonjhon, R G (Plant Science Today, 2025)
Rice terraces, renowned for their agricultural and cultural significance, are found across Southeast Asia, South America and Africa. Despite their resilience, these landscapes face threats from climate change, land-use changes and declining traditional knowledge. In the Philippines, the Cordillera rice terraces, a United Nations Educational, Scientific and Cultural Organization (UNESCO) world heritage site, suffer from land abandonment, pest infestations and insufficient government support yet technical stability assessments remain limited. The Maligcong rice terraces, like many traditional systems, experience instability, but comprehensive studies on their structural integrity are scarce. This study investigates the stability of these terraces by linking soil properties, terrace geometry and the factor of safety (FoS). Soil characterization revealed predominantly sandy compositions with varying moisture content and hydraulic conductivity across layers. Non-invasive techniques, including portable in-situ soil testing and geophysical methods (geo resistivity), effectively captured soil properties. Drone surveys integrated with Agisoft Metashape and Civil 3D provided accurate geometric modeling. While geometric parameters such as height and width influence terrace design, statistical analysis showed they had minimal impact on FoS. Instead, groundwater fluctuations, particularly water table rise during rainfall, significantly affected stability by increasing pore water pressure and reducing effective stress. Sensitivity analysis confirmed that the most critical stability parameters-cohesion, friction angle and unit weight are concentrated in the surface layer. This study highlights the vulnerability of rice terraces due to soil strength limitations and hydrogeological factors. The findings emphasize the necessity of integrating soil and water assessments into conservation strategies to ensure the long-term sustainability of these culturally and agriculturally valuable landscapes.